FORMACYJNY WYMIAR ŚWIATOWYCH DNI MŁODZIEŻY - Tkocz, Elżbieta (Studia Katechetyczne, 2016)
The article, in great detail, describes World Youth Day and emphasizes its formational dimension. First of all, the formational dimension is analysed, then the genesis, assumptions and the structure of the WYD celebration and its purpose are discussed. In the more distant part of the article, the author indicates the formational value of these events and the concern about the integral character of the formation that takes place in WYD. The article singles out the doctrinal, liturgical-sacramental, common and apostolic formation. The source of reflection that was provoked are numerous statements of the Popes and addresses on WYD. This analysis clearly states that WYD comprises, as far as content and the structure are concerned, an integral concept of Christian formation. In conclusion, the author lists conditions of the effectiveness of formational actions that take place during WYD which are specific indicators of the chaplaincy.